Perspektif Hukum Pada Hak Moral Pemegang Hak Cipta Yang Berbeda Nama Terhadap Pencipta Yang Masih Hidup - Mustofa Fahmi; Aidul Fitriciada Azhari; Absori; Didik Irawansah (ILIN Institute, 2022)
This study aims, (1) to find out the legal protection of the moral rights of traditional art creators on the recording of a work in Copyright Law; (2) To find out what legal steps can be taken by the Author for the recording of a work in the context of law enforcement in Indonesia. This research method is normative law. Legal approach, case approach and approach, interview research data sources and direct observations and combined with laws and regulations that are closely related to the object of research. Data analysis is descriptive analytical and qualitative withdrawal. The results of the study found a form of legal protection for the rights of the creators of traditional moral arts in the form of performing the basic motion of the Kethek Ogleng dance for recording a work in copyright law in the form of moral rights and economic rights for his creations. Meanwhile, legal steps that can be taken by the author on the recording of the work can be done by recording the change in the name of the right holder, as well as other steps, namely the deletion of the registration of the work to the Minister of Law and Human Rights of the Republic of Indonesia and then re-registering with the creator and rights holder create.